Bridging the gaps towards precision psychiatry: Mechanistic biomarkers for early detection and intervention. (March 2023) - Do, Kim Q.
Highlights: Early detection and intervention, improving prognosis, require mechanistic biomarkers. Mechanism-based biomarkers allow patient stratification, disease monitoring and treatment. Oxidative stress: hub on which genetic & environmental risks converge during development. OxS interaction with dysfunction of dopamine, NMDAR, mitochondria and inflammation. Parvalbumine GABA interneurons, gamma oscillations, critical for cognition. miR-137 and COX6A2: markers of parvalbumin microcircuit impairments. Abstract: Early detection and intervention in schizophrenia, improving prognosis, requires mechanism-based biomarkers that capture circuitry dysfunction, allowing optimized patient stratification, disease monitoring and treatment. Dr. Do's translational research, bridging basic neuroscience and clinical psychiatry, tackles an urgent need to develop effective treatments that target mechanisms underlying cognitive deficits, a critical dimension of schizophrenia, currently not well treated. By adopting a reverse translation of validated circuitry relevant human endpoints, her research brought new insights in mechanism-based biomarker guided treatment of patients in early stages of psychosis. She showed that oxidative stress/redox dysregulation, in reciprocal interaction with dopamine imbalance, NMDAR hypofunction, neuroinflammation and mitochondrial bioenergetic dysfunction, may represent a "hub" on which both genetic and environmental risk factors converge during neurodevelopment. This leads to impairments of structural and functional connectivity in microcircuits, involving impaired parvalbumin fast-spiking GABA neurons, and macrocircuits, impacting myelination of fiber tracts, at the basis of neural synchronization abnormalities, as well as sensory and cognitive deficits. These unique insights led to successful proof-of-concept clinical trials, targeting oxidative stress through antioxidant-based strategies in patients at various disease stages, paving the way for precision medicine in psychiatry.